2017
DOI: 10.1111/iar.12234
|View full text |Cite
|
Sign up to set email alerts
|

U–Pb zircon ages of the Nakanogawa Group in the Hidaka Belt, northern Japan: Implications for its provenance and the protolith of the Hidaka metamorphic rocks

Abstract: Zircon U–Pb ages of two acidic tuff and two turbidite sandstone samples from the Nakanogawa Group, Hidaka Belt, were measured to estimate its depositional age and the development of the Hokkaido Central Belt, northeast Japan. In the northern unit, homogeneous zircons from pelagic acidic tuff from a basal horizon dated to 58–57 Ma, zircons from sandstone from the upper part of the unit dated to 56–54 Ma, and zircons from acidic tuff from the uppermost part dated to 60–56 Ma and 69–63 Ma. Both of the tuff U–Pb a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 36 publications
(140 reference statements)
1
33
0
Order By: Relevance
“…Cretaceous accretionary complexes in Hokkaido are dominated by greenstone of various origins, such as seamounts, normal oceanic crust, oceanic plateau material and island arcs (Ueda & Miyashita, ). In contrast, the Paleocene–Eocene complexes are dominated by terrigenous sediments (Kiminami & Kontani, ; Nanayama, ; Nanayama et al, ). The in situ eruption of mid‐oceanic ridge type basaltic magma (MORB) into the Paleogene accretionary complex has been reported (Miyashita & Yoshida, ) and it was suggested that the Kula‐Pacific ridge–trench encounter occurred during the Paleocene.…”
Section: Early Cenozoic Geological Gap Other Than the Shimanto Belt Imentioning
confidence: 99%
“…Cretaceous accretionary complexes in Hokkaido are dominated by greenstone of various origins, such as seamounts, normal oceanic crust, oceanic plateau material and island arcs (Ueda & Miyashita, ). In contrast, the Paleocene–Eocene complexes are dominated by terrigenous sediments (Kiminami & Kontani, ; Nanayama, ; Nanayama et al, ). The in situ eruption of mid‐oceanic ridge type basaltic magma (MORB) into the Paleogene accretionary complex has been reported (Miyashita & Yoshida, ) and it was suggested that the Kula‐Pacific ridge–trench encounter occurred during the Paleocene.…”
Section: Early Cenozoic Geological Gap Other Than the Shimanto Belt Imentioning
confidence: 99%
“…Recently, the age of Hidaka Group was revised from pre‐Tertiary to Paleogene by Nanayama et al . (). Figure is the geological map of Itomuka area based on these previous studies.…”
Section: Geological Settingmentioning
confidence: 97%
“…Geological map of the Itomuka mercury mine (modified after Sugimoto et al ., , the age of Hidaka Group is taken from Nanayama et al ., ). Line A‐A′ shows the section line in Figure …”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations